Faktor-Faktor Sosial yang Mempengaruhi Keputusan Pembelian Konsumen Minimarket Indomaret dengan Minimarket Biasa - Muhammad Iqbal Ramadhan; Mohammad Alqadri Perdana (JURNAL PETISI (Pendidikan Teknologi Informasi), 2020)
Consumer decisions are processes that occur to consumers when he decides to buy, what to buy, where, when and how to buy it. This study aims to determine the factors that influence consumer decisions in choosing Indomaret minimarkets and ordinary minimarkets and the most dominant factors that influence consumer decisions in choosing the Indomaret minimarket with ordinary minimarkets in the city of Bengkalis. This type of research is observational. This study uses the method of qualitative analysis, quantitative analysis and perception analysis. The results of this study indicate that consumer decisions that are influenced by the social factors of Indomaret minimarket are personality factors with a value of 3.37 and consumer decisions that are influenced by social factors of Indomaret minimarket are reference group factors with a value of 3.49. From the results of the research that has been obtained it turns out that reference groups, family factors, personality factors influence decisions, the most dominant factors are reference group factors and personality factors. While the lowest factor, namely personality factors 2.69.